DINAMIKA PENETAPAN WAKIL GUBERNUR KEPULAUAN RIAU SISA MASA JABATAN 2016-2021 - Afdal "; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted with the aim to find out the dynamics that occur in the determination of the Deputy Governor of Riau Islands remaining the term of office 2016-2021. Since the appointment of Deputy Governor of Riau Islands to be the definitive Governor there has been a vacancy of Deputy Governor for 1 (one) Year 8 (eight) months, arousing a sense of curiosity about the delay in the process of filling in the Deputy Governor of Riau Islands and the dynamics in the Deputy Governor of Riau Islands. 2016-2021 positions.The absence of a Government Regulation on the procedure for filling the Deputy Governor's vacancy at that time made the process long because the special committee did not have guidelines in the formulation of regulations so that it had to consolidate with the Ministry of Home Affairs, KPU and legal and political experts in drafting the rules and bearers the authority to propose 2 (two) names of Deputy Governor candidates who will be proposed to the Riau Islands Provincial DPRD failed to find an agreement in determining 2 (two) names of Deputy Governor candidates, until the final limit for nominating candidates is only 1 (one). others did not qualify because they did not get the recommendation of the bearer party.The theory used in this study is contestation theory, competition theory and the concept of dynamics. This study uses descriptive analytical methods with a type of qualitative research. The type of data used in this study are primary data and secondary data obtained through direct interviews with informants who are considered to know and understand the problems that exist in the field, data in the field, documentation and observation.Based on the explanation above, it can be concluded that the length of the process of determining the Deputy Governor of Riau Islands the remaining term of 2016-2021 is due to the issuance of Government Regulations that regulate technically how the election procedures and bearer parties do not find an agreement to propose 2 (two) names of candidates for Deputy Governor . prospective deputy governor to be determined at the plenary session of the Riau Islands Province DPRD.Keywords: Dynamics, Deputy Governor